2015
DOI: 10.1038/ijo.2015.139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term treatment with testosterone on weight and waist size in 411 hypogonadal men with obesity classes I-III: observational data from two registry studies

Abstract: Background/Objectives:Long-term testosterone replacement therapy (TRT) up to 5 years has been shown to produce progressive and sustainable weight loss (WL) in hypogonadal men. This study investigated effects of long-term TRT up to 8 years in hypogonadal men with different obesity classes.Subjects/Methods:From two independent observational registries we identified a total of 411 obese, hypogonadal men receiving TRT in urological clinics. The effects of TRT on anthropometric as well as metabolic parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 60 publications
9
101
1
8
Order By: Relevance
“…With respect to triglycerides, in type 2 diabetic patients with hypogonadism, TU therapy produced a decrease of 62 mg/dL at 12 months [7], and up to 138 mg/dL at 8 years [9]. In the present study, the drop observed at 22 weeks versus placebo was 59.9 mg/dL, a figure similar to that found in type 2 diabetes.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…With respect to triglycerides, in type 2 diabetic patients with hypogonadism, TU therapy produced a decrease of 62 mg/dL at 12 months [7], and up to 138 mg/dL at 8 years [9]. In the present study, the drop observed at 22 weeks versus placebo was 59.9 mg/dL, a figure similar to that found in type 2 diabetes.…”
Section: Resultssupporting
confidence: 74%
“…Testosterone replacement therapy in type 2 diabetes patients with hypogonadism produced a significant reduction in insulin resistance and glycosylated hemoglobin [6][7][8] as well as an improvement in anthropometric parameters and a drop in blood pressure [9,10], being controversial the impact on lipid profile [6,7,9,[11][12][13][14].…”
mentioning
confidence: 99%
“…The last 2 decades have witnessed a revolution in medical management of men with testosterone (T) deficiency (TD; also known as hypogonadism) [123456789101112131415]. TD has been recognized for more than 7 decades [161718] and T therapy has been used clinically, as early as 1940, both in men and women [161718].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients suffering from congestive heart failure (Jankowska et al 2006) and coronary artery disease (Li et al 2012) have been shown to have lower levels of testosterone compared with healthy men, and the severity of these conditions had a strong correlation with the degree of testosterone deficiency (Li et al 2012, Oskui et al 2013. Recent clinical studies demonstrated that testosterone replacement could improve insulin sensitivity, increase lean mass, and decrease subcutaneous fat (Dhindsa et al 2016) and also improve cardiometabolic parameters in type 2 diabetes men with testosterone deprivation (Hackett et al 2014) and in hypogonadal men with metabolic syndrome (Saad et al 2016).…”
Section: Metabolic Disturbancementioning
confidence: 99%